A REVIEW: SIGNIFICANCE OF DOOSHIVISHA IN CURRENT ERA W.S.R TO BIOACCUMULATION OF ENVIRONMENTAL TOXINS - Kakde Suvarna Suryakant (International Journal of Applied Ayurved Research, 2017)
In Ayurveda the spectrum of ‘Dooshivisha’ concept is expounded in many ways. It can be applied to cumulative poisoning which is very common in today’s era. Dooshivisha is less potent part of sthavar, jangama or krutrim visha which is not fully eliminated from body & vitiates dhatus when favorable conditions occur. In the modern era human body gets exposed to large number of poisonous substances due to industrialization, use of chemicals and agriculture. Heavy metal compounds, pesticides, some preservatives are accumulated in the body through contaminated air, water, soil & food. The heavy metal once absorbed, compete with other ions & bind to proteins resulting in impaired enzymatic activity resulting in damage to many organs throughout the body. Prolong use of certain medicines, cosmetics, cleaning products also caused cumulative poisoning. Bioaccumulation refers to the accumulation of substances, such as pesticides, other organic or inorganic chemicals in organism. Bioaccumulation occurs when an organism absorbs possibly toxic substances at a rate faster than that at which the substance is lost by catabolism & excretion.By using the concept Dooshivisha & bioaccumulation, we can properly understand the risk of cumulative poisoning caused by environmental toxins & treat them accordingly.